2020
DOI: 10.1177/1747021820942687
|View full text |Cite
|
Sign up to set email alerts
|

Performing a task jointly enhances the sound-induced flash illusion

Abstract: Our senses are stimulated continuously. Through multisensory integration, different sensory inputs may or may not be combined into a unitary percept. Simultaneous with this stimulation, people are frequently engaged in social interactions, but how multisensory integration and social processing interact is largely unknown. The present study investigated if, and how, the multisensory sound-induced flash illusion is affected by a social manipulation. In the sound-induced flash illusion, a participant typically re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 65 publications
(110 reference statements)
0
8
0
Order By: Relevance
“…While the present study investigated the impact of joint attention on the sound-induced flash illusion, an earlier study found that a division of labour manipulation, where the participant reported on the number of flashes while a confederate simultaneously reported on the number of beeps, induced a stronger fission illusion compared with performing the task alone (Wahn et al, 2020). The authors suggest that in their social manipulation, the participant's visual attention was divided between the visual flash-counting task and attending to the co-actor, which in turn increased the influence of the auditory stimuli and thus the number of perceived fission illusions.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…While the present study investigated the impact of joint attention on the sound-induced flash illusion, an earlier study found that a division of labour manipulation, where the participant reported on the number of flashes while a confederate simultaneously reported on the number of beeps, induced a stronger fission illusion compared with performing the task alone (Wahn et al, 2020). The authors suggest that in their social manipulation, the participant's visual attention was divided between the visual flash-counting task and attending to the co-actor, which in turn increased the influence of the auditory stimuli and thus the number of perceived fission illusions.…”
Section: Discussionmentioning
confidence: 86%
“…The authors suggest that in their social manipulation, the participant's visual attention was divided between the visual flash-counting task and attending to the co-actor, which in turn increased the influence of the auditory stimuli and thus the number of perceived fission illusions. Since participants in a pair performed different tasks, participants likely showed a tendency to co-represent the other's task and monitor the other's performance (Wahn et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations